Effect of Phytase Supplementation on the Digestibility of Crude Protein, Amino Acids and Phosphorus of Cowpea (Vignia unguiculata) in Broilers - Iyayi , Eustace A. (International Journal of Poultry Science, 2012)
Cowpea contains phytate-P and other nutrients like amino acids which are poorly digested in broilers. Supplementation of such diets with microbial phytase helps to improve digestibility of these nutrients. In 2 experiments the effect of phytase supplementation on the digestibility of crude protein, amino acids and P of cowpea in broilers were investigated. Experiment One, had 6 diets in which 0, 150 or 300 g kg-1 cowpea replaced maize starch and 0 or 500 units of phytase enzyme (Natuphos), in a 3 x 2 factorial arrangement to determine P digestibility and performance of the birds. Experiment Two, had similar diets as in experiment 1 with the objective to determine digestibility of CP and AAs. TiO2 was added as an indigestible marker in the diets and in each of the experiments a total of 288 1-day-old broiler chicks (Ross strain) were used. Phytase supplementation increased (p